Surface Functionalization of Surfactant‐Free Particles: A Strategy to Tailor the Properties of Nanocomposites for Enhanced Thermoelectric Performance. Issue 35 (21st July 2022) - Chang, Cheng; Liu, Yu; Ho Lee, Seung; Chiara Spadaro, Maria; Koskela, Kristopher M.; Kleinhanns, Tobias; Costanzo, Tommaso; Arbiol, Jordi; Brutchey, Richard L.; Ibáñez, Maria
Abstract: The broad implementation of thermoelectricity requires high‐performance and low‐cost materials. One possibility is employing surfactant‐free solution synthesis to produce nanopowders. We propose the strategy of functionalizing "naked" particles' surface by inorganic molecules to control the nanostructure and, consequently, thermoelectric performance. In particular, we use bismuth thiolates to functionalize surfactant‐free SnTe particles' surfaces. Upon thermal processing, bismuth thiolates decomposition renders SnTe‐Bi2 S3 nanocomposites with synergistic functions: 1) carrier concentration optimization by Bi doping; 2) Seebeck coefficient enhancement and bipolar effect suppression by energy filtering; and 3) lattice thermal conductivity reduction by small grain domains, grain boundaries and nanostructuration. Overall, the SnTe‐Bi2 S3 nanocomposites exhibit peak z   T up to 1.3 at 873 K and an average z   T of ≈0.6 at 300–873 K, which is among the highest reported for solution‐processed SnTe. Abstract : A novel strategy of functionalizing the surface of "naked" particles by using inorganic molecules is proposed. In particular, bismuth thiolate were used to functionalize surfactant‐free SnTe particles' surfaces. Upon thermal processing, bismuth thiolates decomposition renders SnTe‐Bi2 S3 nanocomposites with synergistic functions to enhance thermoelectric performance.